Resisting and Negotiating Thanksgiving: A Sociolinguistic and Critical Discourse Analysis of Native American Public Posts on X - Hasyim, Fuad (Smart Edu Center, 2026)
This study analyzes selected public posts on X to examine how Indigenous perspectives on Thanksgiving are discursively performed and negotiated in public digital spaces. While Thanksgiving is commonly portrayed as a harmonious national celebration, Indigenous users frequently reframe it as a symbol of colonization, historical loss, and resistance. Drawing on a sociolinguistic perspective informed by language attitudes theory and Critical Discourse Analysis (CDA), the study examines 14 publicly available posts produced by Indigenous individual users and allied organizations. The analysis identifies three recurring discursive patterns. First, dominant historical narratives are openly challenged through linguistic strategies such as hashtags, irony, and references to historical trauma. Second, Indigenous identity is asserted through code-switching, the use of Indigenous language terms, and expressions of community-centered solidarity. Third, ambivalence emerges in posts that reject the colonial foundations of Thanksgiving while simultaneously affirming personal relationships and cultural continuity. The findings underscore the importance of attending to Indigenous voices within contested national narratives and demonstrate how digital platforms function as sites for identity negotiation, resistance, and counter‑historical meaning‑making. The study contributes to ongoing discussions in sociolinguistics and discourse studies on language attitudes, identity construction, and the politics of cultural representation in contemporary American society.